2020
DOI: 10.1371/journal.pone.0239675
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Fabry Disease in patients with unexplained left ventricular hypertrophy

Abstract: Fabry Disease (FD) is a systemic disorder that can result in cardiovascular, renal, and neurovascular disease leading to reduced life expectancy. FD should be considered in the differential of all patients with unexplained left ventricular hypertrophy (LVH). We therefore performed a prospective screening study in Edmonton and Hong Kong using Dried Blood Spot (DBS) testing on patients with undiagnosed LVH. Participants found to have unexplained LVH on echocardiography were invited to participate and subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The present study is the first to systematically investigate the prevalence of FD among a non-selective Han Chinese patient population with LVH. Most previous FD screening studies in the LVH populations were predominantly targeted at non-Asian patients with unexplained and/or severe LVH [ 3 , 4 , 10 , 11 , 12 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Studies adopting a more all-inclusive screening approach generally yielded a low detection rate of less than 1% [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first to systematically investigate the prevalence of FD among a non-selective Han Chinese patient population with LVH. Most previous FD screening studies in the LVH populations were predominantly targeted at non-Asian patients with unexplained and/or severe LVH [ 3 , 4 , 10 , 11 , 12 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Studies adopting a more all-inclusive screening approach generally yielded a low detection rate of less than 1% [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small study identified two patients from a cohort of 79 males with unexplained LGE on CMR, translating to 2.5% [ 5 ]. Another recent study of 266 patients with LVH identified five patients (2%) all with the intronic IVS4 + 919G > A genotype, known to be associated with late onset FD [ 13 ]. These five individuals were all of Chinese origin, a population where the IVS4 + 919G > A variant has a particularly high frequency [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common variant detected in the screening was IVS4+919G>A in Hong Kong and Japan, with a total of 11 individuals carrying this variant [82,92,97]. This variant was frequently detected in NBS in Taiwan and patients with late-onset FD with cardiac manifestations [17].…”
Section: High-risk Screening For Fd In Individuals With Cardiac Manifestationsmentioning
confidence: 98%
“…We reviewed 23 high-risk screenings for FD in individuals with cardiac manifestations (Table 2), with 20 screenings performed for individuals with either LVH or HCM [40,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. The other three screenings were performed in individuals with a variety of cardiac symptoms, including coronary artery disorders, conduction disorders, cardiomyopathy, and valvular disease [99], those with conduction disorders requiring a pacemaker [100], and those with left ventricular noncompaction (LVNC) [101].…”
Section: High-risk Screening For Fd In Individuals With Cardiac Manifestationsmentioning
confidence: 99%